Towards a more effective way of presenting virtual reality museums exhibits - Terlikkas, Constantinos; Poullis, Charalambos (My University, 2014)
In this work, we present the design, development and comparison of two immersive applications with the use of Virtual Reality CAVE technology: a virtual museum following the traditional paradigm for the museum exhibit placement and a virtual museum where no spatial restrictions exist. Our goal is to identify the most effective method of arranging museum exhibits when no constraints are present. Additionally we will present the significance of the folklore museum in cyprus. Since this would affect the design process.
Keywords: Modeling; Virtual reality museums; Visualization; VR systems